Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.). Issue 9 (2nd May 2020) - Bano, Shehar; Intisar, Azeem; Rauf, Mahd; Ghaffar, Abdul; Yasmeen, Farhat; Zaman, Waheed-Uz-; Intisar, Uzma; Kausar, Gulnaz; Muhammad, Nadeem; Aamir, Aqsa
Abstract: Volatile oil composition of leaves and fruits of Terminalia arjuna (Roxb.) was reported for the first time. Oils were extracted by microwave assisted hydrodistillation where yield of both oils were found to be 0.20% and their GC-MS analyses led to the identification of 65 and 48 constituents, respectively. Major constituents of leaves were carvacrol (11.17%), thymol (6.52%), α -terpinyl acetate (5.92%) and anethole (5.13%) while that of fruits were (E)- isoeugenol (11.48%), furfural (8.25%), p -vinylguaiacol (6.8%) and p -ethylguaiacol (5.72%) that demonstrated a significant difference between composition of its aerial parts, however, 33 constituents were identical that showed similarity characteristics in quality of these oils. Both leaf and fruit oils were found active against pathogenic and drug-resistant microbes: E. coli, Methicillin-resistant S. aureus, P. aeruginosa, Total-drug-resistant P. aeruginosa and K. pneumoniae with MIC values of 0.32, 0.32, 0.64, 0.64, 2.56 mg/mL and 0.16, 0.16, 0.32, 0.64, 1.28 mg/mL, respectively. Graphical Abstract: